Sul contenuto delle DAT tra autodeterminazione del paziente e decisioni di altri: profili civilistici (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper aims at highlighting the discrepancy that could emerge between the patient’s will regarding his/her health treatment and the decision taken by a third party, in the event that the former is not able to consent. The paper proposes to integrate the act with external elements through the so-called “relatio”, with the purpose to preserve the patient’s self-determination as well as the third party’s function.
Keywords: Advance decisions; content; enforcement â€œper relationemâ€; current state; trustee